Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Generasi Z dengan Disiplin Kerja sebagai Variabel Mediasi: Pada Unit Vertikal Kantor Wilayah Direktorat Jenderal Perbendaharaan Provinsi Papua - Ardiansyah; Kambuaya, Balthasar; Wanma, Johanis R. (Adhigana Papua: Jurnal Ilmiah Magister Manajemen, 2024)
This study aims to analyze the influence of transformational leadership and organizational culture on the performance of Generation Z employees, with work discipline as an intervening variable in the Vertical Unit of the Regional Office of the Directorate General of Treasury in Papua Province. This research employs an explanatory method with a quantitative approach to explain the causal relationships between variables and test the hypotheses. The research population consists of Generation Z employees aged 20 to 29 years, totaling 89 people, with the entire population serving as the sample. Data collection was conducted through an online questionnaire, and data analysis utilized Structural Equation Modeling-Partial Least Square (SEM-PLS). The results indicate that transformational leadership, organizational culture, and work discipline directly have a significant impact on the performance of Generation Z employees. Furthermore, work discipline serves as an intervening variable that mediates the influence of transformational leadership and organizational culture on the performance of Generation Z employees. These findings provide practical implications for organizational leaders in developing leadership approaches and organizational culture that are more responsive to the needs and characteristics of Generation Z.